2022
DOI: 10.1111/1467-9566.13564
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges for doctors in India: Deprofessionalisation, reprofessionalisation or fragmentation?

Abstract: Western‐trained doctors in India struggled to establish themselves as a medical ‘profession’ in the 1920s and 1930s and these struggles continued into the post‐colonial period. The direction of travel is, however, no longer clear. Increasing evidence of a crisis in doctors’ collective ability to provide a form of self‐regulation since 2000 is highlighted. India’s Supreme Court suspended the operations of their country’s medical councils in the face of a proliferation of poorly regulated private medical college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The staff members' actions also played a role. 26 According to a study, a higher number of cases were reported from public facilities in Delhi and Uttar Pradesh (UP), and Maharashtra and Rajasthan reported more violence from private facilities. 27 Factors leading to violence A.…”
Section: Healthcare Professionals At Riskmentioning
confidence: 99%
“…The staff members' actions also played a role. 26 According to a study, a higher number of cases were reported from public facilities in Delhi and Uttar Pradesh (UP), and Maharashtra and Rajasthan reported more violence from private facilities. 27 Factors leading to violence A.…”
Section: Healthcare Professionals At Riskmentioning
confidence: 99%
“…Social scientists have paid less attention to the dissemination of institutions. Most studies of the medical profession have examined the global north (Jeffery, 2023). Medical specialities in the global south have only received passing mention (e.g., Kumbhar, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Roger Jeffery revisits a short‐lived debate on the professionalisation (or otherwise) of medicine in India that he conducted with Ronald Frankenberg some 40 years ago (Jeffery, 2024). He focuses on the changes in the social, political and economic positions of doctors in India in the 21st century.…”
mentioning
confidence: 99%